Navigated transcranial magnetic stimulation possibilities in difficult diagnostic cases upper motor neuron lesions – case report - I. S. Bakulin; A. V. Chervyakov; M. N. Zakharova; N. A. Suponeva; M. A. Piradov (Нервно-мышечные болезни, 2015)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized with lesions of both upper and lower motor neurons. In accordance with modern diagnostics criteria, only clinical symptoms are used for revealing lesions of the upper motor neuron with the ALS, which often causes serious difficulties. Absence of the pyramidal syndrome does not allow diagnosing ALS, and the diagnosis of progressive muscular atrophy should be set in these cases. We describe a case of an isolated generalized lesion of the lower motor neuron with the signs of cortical motor neurons lesion revealed in the course of navigational transcranial magnetic stimulation. Possible reasons for difficulties in detecting pyramidal syndrome are discussed together with the necessity of working out the criteria of instrumental diagnostics of lesions of the upper motor neuron in ALS.